Building Better Science: A Framework for Discovery and Project-Based Learning in Thermal Physics Education - Zakiah Zakiah; Makawiyah Makawiyah; Mariati Mariati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Project-based learning involves (1) students investigating important ideas and asking questions, (2) finding understanding in the process of investigating, (3) according to their needs and interests, (4) producing products and thinking creatively, (5) being critical and skilled in investigating and concluding material, and (6) connecting with real-world, authentic problems and issues. The Discovery Learning learning paradigm requires the instructor to supervise and steer student learning activities according to the goals—conditions like these desire to shift teaching and learning from teacher-centered to student-centered. R&D and experimentation are used in this study. After the research, statistics were used to compare student learning results from both practicum guides with distinct approach strategies. The Discovery practicum guide is the independent variable. Project-based learning and character qualities, whereas student learning results are the dependent variable. The average pretest score in Experimental Class I and II, Discovery Model practical guideIn a row, the Project-Based Learning Model is 53.00±8.65183375 and 56.00±11.91704748The average posttest score in Experimental Class I, Discovery model practical guide, and Experimental Class II, practical guideProject Based Learning Model: 86.00±9.045920836, 81.75±13.95110653. Establishing the normalized gain value of scientific learning outcomes in the class was important since students' average pretest and posttest scores in the science experiment differed. The Discovery Model practical guide is more successful for teaching and learning, particularly for heat and explanation information, than the Experimental Model. Project-based learning is best with the Discovery Model practical guide.